Corrosion reaction and hydrogen absorption of steel for prestressed concrete in a 20 mass% ammonium thiocyanate solution. (June 2015) - Ichiba, Mikiyuki; Sakai, Jun'ichi; Doshida, Tomoki; Takai, Kenichi
Abstract : It has been proposed that several corrosion reactions occur in the FIP (Fédération International de la Précontrainte) test when using a 20 mass% ammonium thiocyanate solution. The results of the present study show that a cathodic reaction accompanying the decomposition of SCN − ions contributes significantly to hydrogen absorption in the FIP test environment. The cathodic reaction continues even during the period when a gradual decline is seen in the hydrogen content of PC steel specimens in the FIP test.